Respuesta :

Answer:

11102 x^2

Step-by-step explanation:

Simplify the following:

((4 + 1/3)×3×61×6 (3 + 1/2)×4 x x)/6

61/6×6 = (61×6)/6:

(4 + 1/3)×3×(61×6)/6 (3 + 1/2)×4 x x

((3 + 1/2)×4×61×6 (4 + 1/3)×3 x x)/6 = 6/6×(3 + 1/2)×4×61 (4 + 1/3)×3 x x = (3 + 1/2)×4×61 (4 + 1/3)×3 x x:

(3 + 1/2)×4×61 (4 + 1/3)×3 x x

Put 4 + 1/3 over the common denominator 3. 4 + 1/3 = (3×4)/3 + 1/3:

(3 + 1/2)×4×61 (3×4)/3 + 1/3 3 x x

3×4 = 12:

(3 + 1/2)×4×61 (12/3 + 1/3)×3 x x

12/3 + 1/3 = (12 + 1)/3:

(3 + 1/2)×4×61 (12 + 1)/3×3 x x

12 + 1 = 13:

((3 + 1/2)×4×61×13×3 x x)/3

Put 3 + 1/2 over the common denominator 2. 3 + 1/2 = (2×3)/2 + 1/2:

(4×61×13×3 x x)/3 (2×3)/2 + 1/2

2×3 = 6:

((6/2 + 1/2)×4×61×13×3 x x)/3

6/2 + 1/2 = (6 + 1)/2:

(4×61×13×3 x x)/3 (6 + 1)/2

6 + 1 = 7:

(7×4×61×13×3 x x)/(2×3)

(7×4×61×13×3 x x)/(2×3) = 3/3×(7×4×61×13 x x)/2 = (7×4×61×13 x x)/2:

(7×4×61×13 x x)/2

4/2 = (2×2)/2 = 2:

7×2×61×13 x x

7×2×61×13 x x = 7×2×61×13 x^2:

7×2×61×13 x^2

7×2 = 14:

14×61×13 x^2

14×61 = 854:

854×13 x^2

854×13 = 11102:

Answer:  11102 x^2